Design and implementation of an impressed current cathodic protection system for buried metallic pipes (part II) (considering Al-Quds gas station in Baghdad) - Saif al deen H Mohammed; Isam M Abdulbaqi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this part, the implementation of the Cathodic Protection (CP) station in a new position is done due to the analytical study of the part (I) [1]. Also, a PV fed self-adjusted DC-DC converter is designed and implemented for this purpose, and Aluminum anodes designed and manufactured for the sake of approving the proposed CP station operation. A field test shows enhanced results due to the National Association of Corrosion Engineering NACE standard. An edit has been made on the main empirical formula that is previously intended for the design of the same CP system. The proposed CP station is very flexible, more accurate, of lower cost, and needs little maintenance as compared with the already existing CP station.